How are Certified Child Life Specialists perceived by healthcare professionals?: A call for interprofessional collaboration. - Wittenberg, Brittany M.; Barnhart, Dorothy (Journal of Interprofessional Care)
Certified child life specialists (CCLS) depend on collaboration with healthcare professionals for awareness of patient needs; however, historically other healthcare professionals misunderstand the CCLS role. The purpose of this study was to examine how healthcare professionals perceived the CCLS role and provide implications on the contribution of the CCLS to interprofessional collaboration (IPC). This study was a partial replication of two previous survey studies. Participants (N = 67) consisted of 26 child life and 42 other healthcare professionals who were employed at one freestanding children's hospital in the southern United States. Qualitative analyses revealed CCLS responsibilities could be explained with seven categories. Child life professionals were more likely to report CCLS responsibilities as providing patient support and family support and documenting psychosocial assessment and interventions in the medical record than other healthcare professionals. Child life and other healthcare professionals are mostly aligned in their perception of the CCLS role, specifically patient education, play, and normalization and development. Previous misconceptions about the CCLS role may be diminishing among other healthcare professionals; however, continued education about the CCLS role and communication with CCLSs would likely promote IPC.